Prediction of Recurrent Emergency Department Visits in Patients With Mental Disorders - Slankamenac, Ksenija; Heidelberger, Raphael; Keller, Dagmar I. (Frontiers in Psychiatry, 2020)
Background: Patients with mental disorders are more likely to be frequent emergency department (ED) users than patients with somatic illnesses. There is little information about recurrent ED visitors (≥ four ED visits/year) due to mental health problems in Switzerland. Therefore, our aim was to investigate the prevalence of recurrent ED visits due to mental disorders and to determine which mental disorders and risk factors were associated with recurrent ED visits. Methods: In a retrospective analysis, we investigated patients suffering from mental health problems between January and December 2015 who presented more than once in the ED of a tertiary care hospital. ED patients who sought out the ED due to mental disorders were grouped in a recurrent group with at least four ED visits per year or in a control group visiting the ED twice or three times within a year. The primary endpoint was to assess the prevalence of recurrent ED patients due to acute symptoms of mental disorders. As secondary endpoints, we investigated which mental disorders and risk factors were associated with recurrent ED visits. Results: Of 33,335 primary ED visits, 642 ED visits (1.9%) were by 177 visitors suffering from acute mental health problems. Forty-five (25.4%) of these 177 patients were recurrent ED visitors; 132 (74.6%) visited the ED twice or three times (control). Patients with personality disorders had a four-times higher risk (p=0.011) of being a recurrent ED visitor. Recurrent ED visitors with mental disorders had significantly more in-house admissions (p<0.001), self-mutilations (p<0.001), acute drug toxicity (p=0.007) and were more often persons of single status (p=0.045). Although recurrent ED visitors more often had an outpatient general physician or psychiatrist, they visited the ED more frequently within office hours (p<0.001). Conclusion: A quarter of frequent ED users with mental disorders are recurrent ED visitors and were more likely to suffer from personality disorders. Recurrent ED visits are associated with higher rates of self-mutilation, acute drug toxicity and a greater number of in-house admissions.